Peningkatan Penjualan Toko Barang Antik “Retrorika” Surabaya Dalam Pendekatan Business Model Canvas (BMC) - Nabila Birrina Ariani; Vembri Aulia Rahmi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Antiques can be an option for running a business. The public is starting to pay attention to the antique goods business because it has its own value. Many antique collectors use it to do business. This research aims to find out what elements have been implemented by the Retrorika Surabaya antique shop and to find out the elements of the right business model to implement the strategy at the Retrorika Surabaya antique shop. The data sources in this research are primary data and secondary data. Primary data was obtained from interviews and observations carried out at the location. Secondary data is data owned and processed by researchers. The research method used is the qualitative phenomenological method. The problem experienced by the Retrorika antique shop is in its efforts to increase sales and distribution of goods from sellers to buyers. The approach used is a business canvas model in which there are nine elements as a reference in planning and continuing a business. Based on the results of research conducted using qualitative phenomenological methods, it was found that Retrorika has implemented most of the BMC elements such as Value proposition, Channels, Cost Structure, Key Resources and Customer Relationships. However, other elements such as Key Activities, Key Partnerships, and Customer Segments are still not fully optimized. The use of social media and e-commerce platforms has helped in increasing visibility and sales, but a more holistic strategy is still needed to optimize all aspects of BMC. Further discussion revealed that although Retrorika stores have utilized several digital marketing strategies, there are several challenges in terms of inventory management and developing more personalized customer relationships.